2009
DOI: 10.1016/j.bbrc.2009.08.174
|View full text |Cite
|
Sign up to set email alerts
|

An unusual dependence of human herpesvirus-8 glycoproteins-induced cell-to-cell fusion on heparan sulfate

Abstract: Human herpes virus 8 (HHV-8) is known to interact with cell surface heparan sulfate (HS) for entry into a target cell. Here we investigated the role of HS during HHV-8 glycoproteins induced cell fusion. Interestingly, the observed fusion demonstrated an unusual dependence on HS as evident from following lines of evidence: 1) a significant reduction in cell-to-cell fusion occurred when target cells were treated with heparinase; 2) in a competition assay, when the effector cells expressing HHV-8 glycoproteins we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Since ZnOTs treatment resulted in a decreased viral entry and internalization, we decided to investigate its effect on virus free cell-to-cell fusion. To create this scenario in vitro CHO-K1 cells were split into two populations: target cells, and effector cells (Tiwari et al, 2009). Target cells were transfected with the gD receptor Nectin-1 and the luciferase reporter gene under the control of the T7 promoter.…”
Section: Resultsmentioning
confidence: 99%
“…Since ZnOTs treatment resulted in a decreased viral entry and internalization, we decided to investigate its effect on virus free cell-to-cell fusion. To create this scenario in vitro CHO-K1 cells were split into two populations: target cells, and effector cells (Tiwari et al, 2009). Target cells were transfected with the gD receptor Nectin-1 and the luciferase reporter gene under the control of the T7 promoter.…”
Section: Resultsmentioning
confidence: 99%
“…It is thought that HS broadly acts as an attachment factor for many viruses, but some publications indicate that HS may have additional functions during KSHV infection of several cell types. One study reported that HS was required on target HEK293, Chinese hamster ovary (CHO), and human conjunctival epithelial cells in a virus-free fusion assay with effector cells that expressed KSHV gB, gH, and gL, suggesting that HS is involved in the interactions between KSHV glycoproteins and entry receptors (39). A second study used advanced imaging to reveal that upon initial binding to HT1080 fibrosarcoma cells, KSHV colocalized with HS only about half of the time, while colocalization with canonical integrin receptors was much more robust (28).…”
Section: Discussionmentioning
confidence: 99%
“…A smaller number of studies have examined select receptors on some epithelial cell lines, but such a unified model of KSHV receptor usage and mechanism of entry has not yet been assembled for any individual cell line. Soluble heparin or the enzymatic removal of HS from the cell surface inhibits KSHV infection of human embryonic kidney HEK293 cells and human conjunctival epithelial cells, suggesting that HS is required for epithelial cell infection (17,25,38,39). EphA2 is also clearly important for KSHV infection of several cell lines.…”
mentioning
confidence: 99%
“…A standard entry assay was performed as described previously [11,17]. Briefly, HCE cells were seeded at a density of 2×10 4 In addition to an ONPG assay, an entry assay was performed to quantify b-galactosidase expression by insoluble 5-bromo-4-chloro-3-indoyl-b-D-galactosidase (X-gal; Invitrogen, Grand Island, NY, USA) as described previously [17,18]. Briefly, HCE cells were grown in a 6-well plate to 100% confluence and treated with 10 mM of ML-7, ML-9 or blebbistatin, or mock-treated (DMSO) before infection with HSV-1gL86 reporter virus.…”
Section: Viral Entry Assaysmentioning
confidence: 99%